An Evaluation of the Implementation of the Merdeka Belajar Curriculum Program for Pancasila Education at the Junior High School Level Using the Stake Countenance Model - Luthfita Aziza; Riyadi Riyadi; Faisal Madani (Green Publisher Indonesia, 2026)
This study aims to evaluate the implementation program of the Independent Learning Curriculum at the junior high school level in Pancasila Education subjects using the Countenance Stake Model. The research focuses on three main aspects: antecedents, transactions, and outcomes, in order to assess the alignment between the program’s objectives, its execution, and the results achieved. A qualitative descriptive method was employed, involving data collection through observation, interviews, and documentation. The findings indicate that the curriculum implementation has generally met the expected standards, particularly in fostering students’ critical thinking, character development, and active participation. However, several challenges remain, including limited teacher understanding of the curriculum framework, lack of supporting learning resources, and variations in student adaptability. The evaluation results suggest the need for continuous professional development for teachers, provision of adequate learning materials, and a more structured monitoring system. Overall, the Countenance Stake Model provides a comprehensive perspective to identify both the strengths and weaknesses of the curriculum implementation, offering recommendations for improving the effectiveness of Pancasila Education in the Independent Learning Curriculum at the junior high school level